Altered Long- and Short-Range Functional Connectivity Density in Healthy Subjects After Sleep Deprivations - Kong, Dan; Liu, Run; Song, Lixiao; Zheng, Jiyong; Zhang, Jiandong; Chen, Wei (Frontiers in Neurology, 2018)
Objective: To investigate the brain functional organization induced by sleep deprivation (SD) using functional connectivity density (FCD) analysis. Methods: Twenty healthy subjects (12 female, 8 male; mean age, 20.6 ± 1.9 years) participated an experiment of 24h SD design. All subjects underwent the MRI scanand attention network test twice, one is during rested wakefulness (RW) status, and the other is after 24 hours’ acute SD. FCD was divided into the shortFCD and longFCD. Receiver operating characteristic (ROC) curve was used to evaluate the discriminating ability of those FCD differences in brain areas during the SD status from the RW status, pearson correlations was used to evaluate the relationships between those differences and behavioral performances. Results: Subjects at SD status exhibited lower accuracy rate and longer reaction time relative to RW status. Compared with RW, SD had a significant decreased shortFCD in the left cerebellum posterior lobe, right cerebellum anterior lobe and right orbitofrontal cortex, and increased shortFCD in the left occipital gyrus, bilateral thalamus, right paracentral lobule, bilateral precentral gyrus and bilateral postcentral gyrus. Compared with RW, SD had a significant increased longFCD in the right precentral gyrus, bilateral postcentral gyrus and right visuospatial network, and decreased longFCD in the default mode network. The area under the curve values of those specific FCD differences in brain areas were (mean±std, 0.933 ± 0.035; 0.863~0.977). Further ROC curve analysis demonstrated that the FCD differences in those brain areas alone discriminated the SD status from the RW status with high degree of sensitivities (89.19% ± 6%; 81.3% ~ 100%) and specificities (89.15% ± 6.87%; 75% ~ 100%). Reaction time showed a negative correlation with the right orbitofrontal cortex (r = - 0.48, p = 0.032), and accuracy rate demonstrated a positive correlation with the right default mode network (r = 0.573, p = 0.008). Conclusions: The longFCD and shortFCD analysis might be potential indicator biomarkers to locate the underlying altered intrinsic brain functional organization disturbed by SD. SD sustains the cognitive performance by the decreased high-order cognition related areas and the arousal and sensorimotor related areas.